An Analysis of Simile Translation Using Pierini Translation Strategy in Critical Eleven Indonesian Novel into English - Odelia, Risca Jovita (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study was conducted to investigate what translation strategies are used in translating figurative language which is a simile in Indonesian into English in the novel Critical Eleven by Ika Natassa. The theory of simile translation strategies proposed by Pierini is used as the theoretical framework of this research. Moreover, this research uses qualitative research and the method used is descriptive research. The data were classified by identifying and analyzing the strategies used to translate the similes in the source text based on Pierini’s theory. The result of this study shows that all of the strategies that have been used to translate the simile identified in the novel and the dominant strategy used is literal translation or retention of the same vehicle (70,0%) by the translator to translate the simile.